 TINJAUAN YURIDIS TERHADAP PERAWATAN DAN PEMELIHARAAN TAHANAN OLEH PENYIDIK KEPOLISIAN - Aryo Fadlian (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2018)
A Prisoner is a person who is in prisoner to undergo a legal process, either as a suspect or defendant who is prisoner by an investigator or public prosecutor because he is suspected or charged with a criminal offense. In life, during society, a prisoner is considered to have broken the law and therefore a prisoner is given a bad stigma. The Criminal Procedure Code (KUHAP) explains that those who have the authority to detain are Investigators (Polri) and Public Prosecutors (Prosecutors). Underwent a detention process, detainees still have rights that must be fulfilled by the detainee. The research method uses Normative Juridical Research. The results of research in fostering detainees at the Regional Police level (Regional Police) investigators conduct mental, spiritual, and psychological guidance so that prisoners stay awake psychologically. But for feeding prisoners only get food that is given does not meet the humanitarian index, feeding does not meet nutritional adequacy.